The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1186/1472-6831-14-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tongue cleaning on bacterial flora in tongue coating and dental plaque: a crossover study

Abstract: BackgroundThe effects of tongue cleaning on reconstruction of bacterial flora in dental plaque and tongue coating itself are obscure. We assessed changes in the amounts of total bacteria as well as Fusobacterium nucleatum in tongue coating and dental plaque specimens obtained with and without tongue cleaning.MethodsWe conducted a randomized examiner-blind crossover study using 30 volunteers (average 23.7 ± 3.2 years old) without periodontitis. After dividing randomly into 2 groups, 1 group was instructed to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 32 publications
(44 reference statements)
0
46
0
8
Order By: Relevance
“…Patients who participated in the study were thoroughly instructed how to properly clean and store dentures, and were monitored by professionals. Several studies have found that the dorsum of the tongue can act as a reservoir of harmful pathogens and a source of infection, but cleaning of the tongue alone, while reducing the amount of bacteria in the tongue coating, does not contribute to the inhibition of dental plaque formation . To improve oral hygiene and reduce the presence of periodontal pathogens, immersion in alkaline peroxide and ultrasonic vibration can be used as auxiliary agents for cleaning complete dentures …”
Section: Discussionmentioning
confidence: 99%
“…Patients who participated in the study were thoroughly instructed how to properly clean and store dentures, and were monitored by professionals. Several studies have found that the dorsum of the tongue can act as a reservoir of harmful pathogens and a source of infection, but cleaning of the tongue alone, while reducing the amount of bacteria in the tongue coating, does not contribute to the inhibition of dental plaque formation . To improve oral hygiene and reduce the presence of periodontal pathogens, immersion in alkaline peroxide and ultrasonic vibration can be used as auxiliary agents for cleaning complete dentures …”
Section: Discussionmentioning
confidence: 99%
“…The tongue coating score was significantly improved at 4 and 8 weeks in both groups. The tongue coating comprises oral microorganisms, and pathogenic bacteria reside beneath the epithelium and salivary components . It is removed in part by abrasion and autopurification of the tongue surface by food.…”
Section: Discussionmentioning
confidence: 99%
“…The tongue coating comprises oral microorganisms, and pathogenic bacteria reside beneath the epithelium and salivary components. 30…”
Section: Discussionmentioning
confidence: 99%
“…Bordas et al () found that mechanical tongue cleaning for 3 days with or without chemical intervention significantly reduced the number of bacteria on the tongue and in the tongue coating. Matsui et al () reported that the number of total bacteria on the tongue was significantly lower than the baseline after 3 days of tongue cleaning, while the level of tongue coating returned to the baseline. On the other hand, the trial conducted by Quirynen et al () showed that 2 weeks of tongue cleaning reduced the numbers of bacteria on the tongue, but without reaching statistical significance, while the amount of tongue coating was significantly reduced.…”
Section: Inhibition Of Oral Malodormentioning
confidence: 99%
“…Tongue cleaning combined with periodontal treatment improves oral malodor in patients with periodontitis, whereas tongue cleaning is more effective at reducing oral malodor than periodontal treatment in patients with gingivitis (Pham et al, ). Tongue cleaning reduces bacterial numbers (Bordas et al, ; Matsui et al, ) and substrates for putrefaction (Bordas et al, ; Quirynen et al, ), but the effects are transient. Bordas et al () found that mechanical tongue cleaning for 3 days with or without chemical intervention significantly reduced the number of bacteria on the tongue and in the tongue coating.…”
Section: Inhibition Of Oral Malodormentioning
confidence: 99%